Updates in the treatment of ocular allergies - Osmo Kari (Journal of Asthma and Allergy, 2010)
Osmo Kari1, K Matti Saari21Department of Allergology, Skin and Allergy Hospital, Helsinki University Central Hospital, Helsinki, Finland; 2Department of Ophthalmology, University of Turku, Turku, FinlandAbstract: Allergic diseases have greatly increased in industrialized countries. About 30% of people suffer from allergic symptoms and 40%–80% of them have symptoms in the eyes. Atopic conjunctivitis can be divided into seasonal allergic conjunctivitis (SAC) and perennial allergic conjunctivitis (PAC). The treatment of SAC is simple; antihistamines, anti-inflammatory agents, or chromoglycate. In severe cases of SAC, subcutaneous or sublingual immunotherapy is helpful. PAC needs longer therapy, often year round, with mast cell stabilizers, antihistamines, and sometimes local steroids. Atopic keratoconjunctivitis is a more severe disease showing chronic blepharitis often connected with severe keratitis. It needs, in many cases, continuous treatment of the lid eczema and keratoconjunctivitis. Blepharitis is treated with tacrolimus or pimecrolimus ointment. Conjunctivitis additionally needs corticosteroids and, if needed, cyclosporine A (CsA) drops are administered for longer periods. Basic conjunctival treatment is with mast cell-stabilizing agents and in addition, antihistamines are administered. Vernal keratoconjunctivitis is another chronic and serious allergic disease that mainly affects children and young people. It is a long-lasting disease which commonly subsides in puberty. It demands intensive therapy often for many years to avoid serious complicating corneal ulcers. Treatment is mast cell-stabilizing drops and additionally antihistamines. In relapses, corticosteroids are needed. When the use of corticosteroids is continuous, CsA drops should be used, and in relapses, corticosteroids should be used additionally. Nonallergic eosinophilic conjunctivitis (NAEC) is a less known, but rather common, ocular disease. It affects mostly middle-aged and older women. The eye symptoms of NAEC are largely similar to those seen in chronic allergic conjunctivitis. Basic therapy is mast cell-stabilizing drops. Eosinophilic inflammation needs additional corticosteroids. In severe cases, CsA drops are recommended. Antihistamines should be avoided. It is important to recognize the different forms of allergic ocular diseases and to start the treatment early and intensively enough to avoid chronicity of the disease and accompanying tissue destruction. Keywords: allergic conjunctivitis, allergic blepharitis, atopic keratoconjunctivitis, eosinophils, vernal keratoconjunctivitis